O protagonismo feminino no Campus Manaus Centro: a inclusão de alunas no contexto do estágio profissional - Silva, Joelma Paz da (2023)
The research addresses the difficulties of inclusion in the world of work within the scope of professional training, highlighting the relevance of internships. The internship often represents the first contact with professional experience, introducing challenges when entering technical areas. The research aims to deconstruct gender inequalities, especially in the area of Mechanics, where students face obstacles, despite the legislation that supports the internship as an educational principle. The study falls within the line of Organization and Memories of Pedagogical Spaces in Professional and Technological Education, within the macro project on formal and non-formal spaces in the world of work and social movements. The conceptual basis of Professional and Technological Education (EPT) guides the research, which seeks to integrate technical training, gender, internship and the world of work as a historical construction over time. The central scientific problem is to investigate the influence of gender on inclusion for the curricular internship in the Mechanics of Technical Professional Education course at the secondary level in the subsequent CMC modality. The objectives include understanding the processes of inclusion and participation of students, analyzing gender relations in the internship, identifying the difficulties faced by students when entering the world of work, describing social barriers and developing an educational product linked to the research results. The method used was a single case study, a qualitative approach involving students, graduates, teachers, administrative technicians and internship integration agents. Data collection was carried out through prolonged interviews, conversation circles, participant observation and field diaries. The analysis of the results was conducted through Content Analysis, culminating in the creation of an educational booklet. This booklet aims to promote debates about female participation in the world of work, highlighting advances and challenges, providing guidance for professional internship students at the Manaus Centro Campus.